Prospective, Randomised Two Centre Trial of Endovascular Repair of Abdominal Aortic Aneurysm With or Without Sac Embolisation. (February 2021) - Fabre, Dominique; Mougin, Justine; Mitilian, Delphine; Cochennec, Frederic; Garcia Alonso, Carlos; Becquemin, Jean-Pierre; Desgranges, Pascal; Allaire, Eric; Hamdi, Sarah; Brenot, Philippe; Bourkaib, Riyad; Haulon, Stephan
Abstract : Objective: The benefit of aneurysm sac coil embolisation (ASCE) during endovascular aortic repair (EVAR) of abdominal aortic aneurysm (AAA) remains unclear. This prospective randomised two centre study (SCOPE 1: Sac COil embolisation for Prevention of Endoleak) compared the outcomes of standard EVAR in patients with AAA at high risk of type II endoleak (EL with EVAR with ASCE during the period 2014–2019. Methods: Patients at high risk of type II EL were randomised to standard EVAR (group A) or EVAR with coil ASCE (group B). The primary endpoint was the rate of all types of EL during follow up. Secondary endpoints included freedom from type II EL related re-interventions, and aneurysm sac diameter and volume variation at two year follow up. Adverse events included type II EL and re-interventions. CTA and Duplex ultrasound scans were scheduled at 30 days, six months, one year, and two years after surgery. Results: Ninety-four patients were enrolled, 47 in each group. There were no intra-operative complications. At M1, 16/47 early type II EL occurred (34%) in group A vs. 2/47 (4.3%) in group B ( p  < .001). At M6, 15/36 type II EL (41.7%) occurred in group A vs. 2/39 (4.26%) in group B ( p  < .001). At M12, 15/37 type II El (40.5%) occurred in group A vs. 5/35 (14.3%) in group B ( p  = .018). At 24 months, 8/32 type 2 El (25%) occurred in group A vs. 3/29 (6.5%) in group B ( p  = .19). Kaplan–Meier curves of survival free from EL and re-interventions were significantly in favour of group B ( p  < .001). Aneurysm sac volume decreased significantly in group B compared with group A at M6 ( p  = .081), at M12 ( p  = .004), and M24 ( p  = .001). Conclusion: For selected patients at risk of EL, ASCE seems effective in preventing EL at one, six, and at 12 months. However, the difference was not statistically significant at 24 months. ASCE decreases the re-intervention rate two years after EVAR. A significantly faster aneurysm volume shrinkage was observed at one and two years following surgery. (SCOPE 1 trial: NCT01878240 )